Pelatihan Storytelling Berbasis Kearifan Lokal untuk Peningkatan Karakter Positif Siswa PAUD Anbiya Walmursalin - Tanti Sugiharti; Dwi Indah Kartika; Soegeng Wahyoedi; Martiman S. Sarumaha; Ria Saraswati; Febrianti Yuli Satriyani; Dety Mulyanti (Pusat Riset dan Inovasi Nasional, 2025)
This study presents the conceptual foundation and objectives of a storytelling training program that leverages Sundanese local wisdom as a pedagogical tool to enhance positive character development among early childhood learners. Employing participatory and practice-oriented methodologies, the training yielded significant improvements in educators’ understanding and instructional competencies, alongside observable benefits in children's character formation. The findings highlight the pedagogical value of integrating indigenous cultural values into early childhood education curricula as a strategic approach to cultivating morally grounded future generations. The urge for this initiative arises from the pressing need to instill positive character traits from an early age, particularly in the context of globalization, which poses a threat to the preservation of local cultural heritage. Prior research has underscored the critical role of local wisdom in character education. Within the contemporary educational discourse, there is an increasing emphasis on guarding traditional values while navigating global cultural shifts. This article particularly examines storytelling as a culturally responsive and effective pedagogical method for embedding Sundanese moral and ethical values into early childhood education, thereby fostering holistic character development.